Analisis Pengembangan Bahan Ajar Pendidikan Agama Islam Berbasis PowerPoint sebagai Media Grafis Digital di Sekolah Menengah Pertama (SMP) melalui Studi Kepustakaan - Hapid Muslih; Siti Fatimatuzzahro; Rika Haulina; Rifdaa Aulia; Dicky Alfian Nur Rachman; M. Imam Riziek Sihabi (Al-Munawwarah : Jurnal Pendidikan Islam, 2026)
This study was motivated by the fact that conventional methods still dominate despite the development of digital technology, which demands innovation in learning, including Islamic Religious Education in junior high schools. The purpose of this study is to analyze the development of Islamic Religious Education teaching materials as graphic media in junior high schools in response to the demands of technological advancements. This study employs a qualitative approach using a literature review. Primary data consists of Islamic Religious Education instructional media and textbooks, while secondary data is derived from scholarly articles on the use of PowerPoint in Islamic Religious Education instruction. Data analysis utilizes the Miles and Huberman model, which includes data reduction, data presentation, and drawing conclusions. The results of the study indicate that PowerPoint is considered effective as a structured interactive digital teaching material that integrates text, audio, and visuals. This multimedia integration has the power to clarify abstract material, maintain focus, and contribute significantly to student motivation and learning outcomes. This effectiveness is closely tied to the quality of communicative visual design, the appropriateness of the material, educators’ competence in designing and creating media, and the support of the school’s digital infrastructure.